PERAN KARAKTERISTIK PEKERJAAN, CAREER PLATEAU TERHADAP KOMITMEN ORGANISASIONAL MELALUI KEPUASAN KERJA DENGAN MODERASI DUKUNGAN ATASAN (STUDI PADA GURU SMA NEGERI RAYON 01 KABUPATEN DEMAK) - 11.52.02.0131, Nurul Khayati (Jurnal Mahasiswa Pasca Sarjana, 2013)
This research aims to analyze the influence of the role of career plateau and job characteristics on organizational commitment through job satisfaction with moderation supervisory support to teachers of SMA Rayon 01 in Demak. Object of this study is the teachers Rayon 01 SMA Demak. Collection method used was purposive sampling method and questionnaire by sending a questionnaire to the respondent. After the data is collected and analyzed using SPSS 16.0. There are 92 respondents had participated in this study. Using Multiple Regression technique, results of this study that the characteristics of the job generating positive and significant effect on job satisfaction , career plateau and a significant negative effect on job satisfaction, job characteristics and significant positive effect on organizational commitment, career plateau, and a significant negative effect on oeganisasional commitment, job satisfaction and a positive effect significant impact on organizational commitment, supervisor support moderates the influence of career plateau on job satisfaction and that also moderate organizational commitment as well. Keywords : job characteristics, career plateau, job satisfaction, organizational commitment, supervisor support.